"Poems in the Entrance Area": Using Photo-Stories to Promote HIV Medication Adherence. Issue 4 (July 2018) - Teti, Michelle; Hayes, Deana; Farnan, Rose; Shaffer, Victoria; Gerkovich, Mary
Adherence to antiretroviral medication among people living with HIV (PL-HIV) is critical to individual and public health. By some estimates only a quarter of PL-HIV are sufficiently adherent, underscoring a continued need for adherence-promoting strategies. In this analysis we explore the effect of adherence education posters developed via Photovoice. A group of PL-HIV generated images and captions to describe their adherence experiences and used their photo-stories to design 10 posters. We assessed viewers' ( N = 111) adherence knowledge, self-efficacy, and communication changes quantitatively and qualitatively before and 3 months after poster placement in the clinic. We analyzed quantitative data with an independent groups t test or a Mann–Whitney test, and qualitative interviews via theme analysis. Quantitative findings indicated no significant differences. Qualitative interviewees said that posters enhanced knowledge with nonthreatening, relatable information; self-efficacy by motivating patients to take medicine and disclose HIV to others; and communication by facilitating adherence conversations and creating a visually supportive clinic. Divergent quantitative and qualitative findings can be partially explained by inquiry methods. The posters may be more effective as part of discussions about their content, like those facilitated by qualitative interviews. Additional research regarding the application of Photovoice to health promotion is warranted.